(untitled) (Nexus International Journal of Science and Education, 2024)
This study examined the relationship between the leadership practices of Principals and the professional commitment of Kinder-Teachers in Nabunturan District, Davao De Oro Schools Division. The research design used was non-experimental descriptive-correlational, and an adapted survey instrument was used to collect responses from randomly selected teacher- respondents. The study found that the extent of the Principal’s leadership practices in resource allocation, collaboration beyond school, and monitoring progress was often demonstrated. However, teacher leadership and data-driven practices were only occasionally demonstrated.Similarly, the professional commitment of Kinder-Teachers in terms of advocacy, parent engagement, continuous learning, and adaptability was often demonstrated, while curriculum development was only occasionally demonstrated. The study found a significant relationship between Principal’s leadership practices and Kinder-Teacher’s Professional Commitment. All domains of Principal’s leadership practices significantly influenced Kinder-Teacher’s Professional Commitment. Future research may investigate the long-term impact of enhanced leadership practices on teacher commitment and student outcomes